Expression profile of ghrelin and ghrelin receptor in cyclic goat ovary - Chandra, Vikas; Ram, Hira; Sharma, A K (The Indian Journal of Animal Sciences, 2012)
Ghrelin, a 28-amino acid acylated peptide, was identified as the endogenous ligand for the GH secretagogue receptor and recently the role of ghrelin in reproduction was established. Total RNA was extracted from corpus luteum (CL) of the slaughterhouse derived goat ovaries of different stages of cyclicity. First strand cDNA synthesis was done using constant quantity of total RNA (8µg / 20 µl reaction mixture) and M-MuLV-RT at 36°C for 1h. Semi quantitative PCR analysis as well as real time PCR (Q-PCR) analysis revealed, persistent expression of ghrelin and its receptor throughout the estrous cycle. Ghrelin mRNA corresponded the activity of CL i.e. minimum expression in the degenerating CL and it was at peak in the fully grown CL and similar trend was also observed for ghrelin receptor. Further, ghrelin and its receptor was absent in prepubertal ovary while it was present in cyclic goat ovaries. It can be concluded that ghrelin may have role in the regulation of ovarian follicular development and early embryonic development.